Combination of polymorphisms within 5' and 3' untranslated regions of thymidylate synthase gene modulates survival in 5 flourouracil-treated colorectal cancer patients - Fernández Contreras, María Encarnación; Sánchez Hernández, J.J.; González, E.; Herráez, B.; Domínguez, I.; Lozano, M.; De Paredes, M.L.; Muñoz, A.; Gamallo, C. (My University, 2009)
In the present study we explored the effect of three polymorphisms of the TS gene on overall and progression-free survival of colorectal cancer (CRC) patients subjected to 5FU chemotherapy. A 28 bp variable number of tandem repeats (VNTR), a G/C single nucleotide polymorphism (SNP), and a deletion of 6 bp at position 1494 were studied. The possible combined effect of these DNA polymorphisms on the clinical outcome of patients was also evaluated. A retrospective study was carried out on paraffin-embedded sections from 113 patients diagnosed of advanced CRC. TS genotyping methods were polymerase chain reaction (PCR) for VNTR and PCR, followed by restriction length fragment polymorphism (PCR-RFLP) for SNP and ins/del 6 bp. To study the combined effect of TS polymorphisms, four categories were defined accordingly to the level of expression attributed to SNP and ins/del 6 bp genotypes: C&allele 6-, C&6+/6+, G&allele6- and G&6+/6+. VNTR and ins/del 6 bp genotypes varied with tumour anatomical site: 2R/2R genotype was rare in left-sided tumours (7.0% vs. 26.3% of right-sided and 24.1% of rectal cancers; P<0.01), where the variant allele 6- was very frequent (69.0%). Instead, most patients with right-sided tumours were wild-type homozygous 6+/6+ (63.9%) (P<0.01). Heterozygous 6+/6- genotype was more frequent among tumours classified as C (50.0%) and D (76.5%) Dukes stages (P=0.05). None of the studied polymorphisms alone affected overall or progression-free survival (PFS). C&6+/6+ and G&6+/6+ combined genotypes were respectively associated to the best and worst PFS (P=0.03 when compared with each other), while combinations carrying the allele 6- determined an intermediate evolution that might be indicative of a variable response to chemotherapy. The rate of Dukes B stage tumours was unexpectedly high (59.1%) among patients with the unfavourable G&6+/6+ combination. In our study the combination of high TS expression genotypes G&6+/6+ identifies a group of high risk within CRC patients treated with 5FU.